Sex-specific differences in cardiovascular risk factors and implications for cardiovascular disease prevention in women - Rajendran, Aardra; Minhas, Anum S.; Kazzi, Brigitte; Varma, Bhavya; Choi, Eunjung; Thakkar, Aarti; Michos, Erin D. (Atherosclerosis, 2023)
Cardiovascular disease (CVD) is the leading cause of mortality for women globally. Sex differences exist in the relative risks conferred by traditional CVD risk factors, including diabetes, hypertension, obesity, and smoking. Additionally, there are female-specific risk factors, including age of menarche and menopause, polycystic ovary syndrome, infertility and the use of assisted reproductive technology, spontaneous pregnancy loss, parity, and adverse pregnancy outcomes, as well as female-predominant conditions such as autoimmune diseases, migraines, and depression, that enhance women's cardiovascular risk across the lifespan. Along with measurement of traditional risk factors, these female-specific factors should also be ascertained as a part of cardiovascular risk assessment to allow for a more comprehensive overview of the risk for developing cardiometabolic disorders and CVD. When present, these factors can identify women at elevated cardiovascular risk, who may benefit from more intensive preventive interventions, including lifestyle changes and/or pharmacotherapy such as statins. This review describes sex differences in traditional risk factors and female-specific/female-predominant risk factors for CVD and examines the role of coronary artery calcium scores and certain biomarkers that can help further risk stratify patients and guide preventive recommendations. [Display omitted] •The relative risk for CVD conferred by traditional risk factors ( diabetes, hypertension, obesity, and smoking) is greater in women compared to men.•Female-specific CVD risk factors include age of menarche and menopause, PCOS, infertility and ART use, pregnancy loss, parity, and adverse pregnancy outcomes. Female-predominant conditions (SLE, RA, and depression) confer additional CVD risk.•Comprehensive risk assessment and selective CAC scoring and/or use of biomarkers can help stratify women's CVD risk and guide prevention efforts.